An algal biostimulant promotes growth and decreases cadmium uptake in accumulator plant Nasturtium officinale. Issue 16 (16th December 2022) - Hu, Rongping; Wang, Hairong; Liu, Qin; Lin, Lijin; Liao, Ming'An; Deng, Honghong; Wang, Zhihui; Liang, Dong; Wang, Xun; Xia, Hui; Tang, Yi
ABSTRACT: The aim of this study was to determine the effects of spraying an algal biostimulant at different concentrations (0, 600-, 900-, 1200-, and 1500-fold dilutions) on the growth and cadmium (Cd) accumulation characteristics of accumulator plant Nasturtium officinale . In a pot experiment, application of the algal biostimulant at all concentrations promoted the growth of N. officinale by increasing the root and shoot biomasses, and the 600-fold dilution of the algal biostimulant had the strongest effect. At all concentrations, the algal biostimulant had no significant effect on the Cd content in roots of N. officinale, and increased the Cd extraction by roots. However, all concentrations of the algal biostimulant except for the 1500-fold dilution decreased the Cd content in shoots and Cd extraction by shoots. The N. officinale plants treated with the 600-fold dilution of the algal biostimulant had the lowest shoot Cd contents and Cd extraction by shoots. The algal biostimulant also increased the contents of photosynthetic pigments (chlorophyll a, total chlorophyll, and carotenoids) in leaves of N. officinale to varying degrees. Different concentrations of algal biostimulant reduced the superoxide dismutase activity, peroxidase activity, and malondialdehyde content of N. officinale, but enhanced the catalase activity, soluble protein content, and relative conductivity. Overall, the 600-fold dilution had the strongest effect on the growth and Cd accumulation characteristics of N. officinale, but did not enhance the phytoremediation ability of N. officinale for growth in Cd-contaminated soil. These results show that this algal biostimulant can promote the growth and reduce the Cd uptake of N. officinale, which is benefit for N. officinale safety production as a wild vegetable in Cd-contaminated soils.